PLANTAS DE CO2 EN DESTILERIAS DE BIOETANOL. “PROCEDIMIENTO INTEGRADOR PARA TOMAR DECISIONES EN CONDICIONES DE INCERTIDUMBRE - González Morales, Víctor Manuel (Centro Azúcar Journal, 2008)
The use of the criteria NPV, IRR, Payback and Analyses of sensitivity in three scenes, to present/display the best alternatives to those who make the decision whether to execute a project of investment or business, has been a habitual practice. In few cases the importance of relating the net Present Value to the amount of the investment that is NPVR (updated Rate of yield) has been considered. An integrating procedure based on a good thought design of alternatives, those that will be discriminated on the base of the calculation of the RVAN. The procedure is explained with details and it is demonstrated with real examples, in CO2 Plants, taken from the author’s practical application.